Concept mapping in introductory physics - Mistades, Voltaire Mallari (Animo Repository, 2009)
Concept mapping is a meta-learning strategy based on the Ausubel-Novak-Gowin theory of meaningful learning. In a concept map, concepts are related with linking words to form propositions. By expanding this concept-proposition link, one eventually forms a web of concepts whose meanings are embedded in the presented map. The paper describes the author's experience with students' use of concept maps and how concept maps are scored. The strategy was utilized as an advance organizer and as an assessment tool (for diagnostic and summative purposes). Sample concept maps constructed by students taking up Introductory Physics are presented.